The first cat in space and the soup of doom - Barnett, Mac; Harris, Shawn (Artist) (New York, NY : Katherine Tegen Books, Harper Alley, 2023)
When the Moon Queen is poisoned by soup, she and First Cat embark on an intergalactic journey to find the antidote in time as secret forces conspire against them, while LOZ 4000 looks for new purpose and meaning in this vast universe.
3.9
3-6
Keywords: Cats -- Comic books, strips, etc; Cats -- Juvenile fiction; Robots -- Comic books, strips, etc; Robots -- Juvenile fiction; Space flight -- Comic books, strips, etc; Space flight -- Juvenile fiction; Poisons -- Juvenile fiction; Moon -- Comic books, strips, etc; Moon -- Juvenile fiction; Adventure stories; Humorous stories; Cats -- Fiction; Robots -- Fiction; Space flight -- Fiction; Poisons -- Fiction; Moon -- Fiction; Adventure and adventurers -- Fiction; Funny animal comics; Action and adventure comics; Graphic novels; Comics (Graphic works)